Welding safety [ (Malvern East, Vic. : Safetycare Australia Pty Ltd, 1992)
This video examines the welding process and safety practices
1. Welding safety -- 2. Oxyacetylene welding & cutting torches -- 3. Arc welding -- 4. Resistance spot welding -- 5. Wire-feed welding
DVD player required
Keywords: Industrial safety; Welding -- safety measures